Identification and Characterization of two new Fungal Pathogens of Polygonatum odoratum (Angular Solomon's seal) in Italy. Issue 11 (19th October 2016) - Karimi, Kaivan; Khodaei, Sima; Rota‐Stabelli, Omar; Arzanlou, Mahdi; Pertot, Ilaria
Abstract: Polygonatum odoratum (Mill.) Druce (Angular Solomon's seal) is a well‐known ornamental plant and herbal drug, which is used in traditional medicine. Severe leaf spots were observed in wild Angular Solomon's seal plants in a public park in Trento, Italy. A combination of morphological and molecular characteristics, including sequence data of ITS‐rDNA, large subunit (LSU), beta tubulin (TUB) and glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) led to identification of two species, namely Phoma odoratissimi and Colletotrichum dematium s. str., isolated from these leaf spots. Pathogenicity of the isolates was confirmed on wounded leaves of Po. odoratum ; indeed, both species induced leaf spot symptoms on inoculated leaves within 10 days of inoculation. This is the first report of leaf spot disease caused by Ph. odoratissimi and C. dematium s. str . on Po. odoratum, which can be considered a new host for both the species examined in this study. In addition, isolation of Ph. odoratissimi represents a new record for the mycobiota of Italy.